Endovascular Therapy Is Effective and Safe for Patients With Severe Ischemic Stroke: Pooled Analysis of Interventional Management of Stroke III and Multicenter Randomized Clinical Trial of Endovascular Therapy for Acute Ischemic Stroke in the Netherlands Data. Issue 12 (December 2015) - Broderick, Joseph P.; Berkhemer, Olvert A.; Palesch, Yuko Y.; Dippel, Diederik W.J.; Foster, Lydia D.; Roos, Yvo B.W.E.M.; van der Lugt, Aad; Tomsick, Thomas A.; Majoie, Charles B.L.M.; van Zwam, Wim H.; Demchuk, Andrew M.; van Oostenbrugge, Robert J.; et al.
Abstract : Background and Purpose—: We assessed the effect of endovascular treatment in acute ischemic stroke patients with severe neurological deficit (National Institutes of Health Stroke Scale score, ≥20) after a prespecified analysis plan. Methods—: The pooled analysis of the Interventional Management of Stroke III (IMS III) and Multicenter Randomized Clinical Trial of Endovascular Therapy for Acute Ischemic Stroke in the Netherlands (MR CLEAN) trials included participants with an National Institutes of Health Stroke Scale score of ≥20 before intravenous tissue-type plasminogen activator (tPA) treatment (IMS III) or randomization (MR CLEAN) who were treated with intravenous tPA ⩽3 hours of stroke onset. Our hypothesis was that participants with severe stroke randomized to endovascular therapy after intravenous tPA would have improved 90-day outcome (distribution of modified Rankin Scale scores), when compared with those who received intravenous tPA alone. Results—: Among 342 participants in the pooled analysis (194 from IMS III and 148 from MR CLEAN), an ordinal logistic regression model showed that the endovascular group had superior 90-day outcome compared with the intravenous tPA group (adjusted odds ratio, 1.78; 95% confidence interval, 1.20–2.66). In the logistic regression model of the dichotomous outcome (modified Rankin Scale score, 0–2, or functional independence), the endovascular group had superior outcomes (adjusted odds ratio, 1.97; 95% confidence interval, 1.09–3.56). Functional independence (modified Rankin Scale score, ⩽2) at 90 days was 25% in the endovascular group when compared with 14% in the intravenous tPA group. Conclusions—: Endovascular therapy after intravenous tPA within 3 hours of symptom onset improves functional outcome at 90 days after severe ischemic stroke. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00359424 (IMS III) and ISRCTN10888758 (MR CLEAN). Abstract : Supplemental Digital Content is available in the text.